Provincial corruption and local development bank performance - Murharsito Murharsito; Fitri Ella Fauziah; Emanuel Kristijadi; Rr. Iramani (Universitas Islam Indonesia, 2017)
This paper investigates the effect of provincial corruption on the performance of local development bank, specifically to the profitability and credit quality. We use the data of 26 local development banks in 2012 and 2013. For the provincial corruption measurement we use “Public Institution Openness Index”. Results of this study are first, corruption significantly has a negative effect on the profitability of local development bank. Second, corruption doesn’t affect the credit quality of local development bank. These results are expected to enrich the within country corruption effect to the economic studies, particularly to the local development bank which is infrequently investigated.